"Qualitative and Quantitative Study of Heavy Metals in Runoff of Highways of Tehran" - J Nouri; KD Naghipour (Tehran University of Medical Sciences, 2002)
Environmental pollution of soil, plants and deposits around highways endanger urban environment through heavy metals as the by-products of vehicles and urban industries along with other pollutants. In this research, three main highways of Tehran city; namely Shahid Chamran, Shahid Hemmat and Yadegar Emam which had the highest rate of vehicle transportation were selected and required sampling was performed in various distances and specific spots. After preparation of the sample by applying standard method, the concentration of 5 metals such as; lead, cadmium, nickel, zinc and copper were measured by means of atomic absorption spectrophotometer-flame absorption. The TSS, TS, sodium and potassium contents were measured as well. The results showed the presence of maximum zinc contents ranging from 0.86 to 5.85 mg l-1 and lead contents of 0.6 to6.5 mg/l, both as the highest metal contents in the three highways. On the other hand, the average concentration of total heavy metals found in the highways were measured for the 5 metals and showed the degree of pollution in Chamran highway, with 3.294 mg/l zinc, 3.06 mg/l lead, 0.210 mg/l copper, 0.127 mg/l nickel and 0.058 mg/l cadmium concentrations. Nevertheless, the heavy metals concentration in Hemmat highway had the minimum amount. It seemed that the high degree of pollution in Chamran highway is due to very heavy and lengthy traffic in this highway, since it is located in the central part of Tehran. It also joins northern part of the city to the downtown area and tolerates a heavy traffic jam of vehicles. In addition, due to the slow traffic move and long stops in Chamran highway, tires undergo more abrasion due to repeated brakes and this intensifies, zinc discharge and lead releases from automobile fuels, all of which are being factors that lead to an increase in the metals contents of runoffs of Chamran highway. The aforementioned subject matters reveal urban management's need to arrange for more controlled and coordination in traffic, environmental preservation and hygiene, particularly in the urban highways.